2015
DOI: 10.1108/bjm-01-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios, their concept, elaboration and application

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Effective PPM leads to: (1) effective allocation/ reallocation of resources, (2) reinforce ment of competitiveness within the fi rm, (3) balanced portfolios that include short-term and long-term projects that cover high-risk and low-risk projects, (4) possible suspension or termination of ineffective members within the project portfolio, (5) use of synergies between projects, (6) development of skills and competencies, (7) unifi cation of terminology, reporting and communication when managing projects and (8) searching for new opportunities for effective projects within investment limits (Fotr & Souček, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Effective PPM leads to: (1) effective allocation/ reallocation of resources, (2) reinforce ment of competitiveness within the fi rm, (3) balanced portfolios that include short-term and long-term projects that cover high-risk and low-risk projects, (4) possible suspension or termination of ineffective members within the project portfolio, (5) use of synergies between projects, (6) development of skills and competencies, (7) unifi cation of terminology, reporting and communication when managing projects and (8) searching for new opportunities for effective projects within investment limits (Fotr & Souček, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Taking into account the abovementioned limitations of the application of the classification method in reducing the number of configuration, it is suggested that a multi-criteria decision -making methods are used to determine test attributes (Fotr, et al 2015). On the other hand, the methods of group decision -making may be used for determining the values of the environmental factors, which can be used for attribute test conditions (e.g.…”
Section: Determination Of Scenario Classes By Using the Classificatiomentioning
confidence: 99%
“…To reduce the number of configurations for each class, using the principle of similarities configuration (Nguyen / Dunn 2009), grouping is carried out and determination of the reference configuration as a representative of the group (Fotr, et al 2015). Clustering methods or cluster analysis is used for the purpose of grouping configuration.…”
Section: Determination Of Representative Configuration Within the Clamentioning
confidence: 99%
See 2 more Smart Citations